Removing limitations surrounding terpenoid biosynthesis by biotechnological techniques in Ferula sp.: A review - Zahra Aghaali; Jun-Li Yang; Mohammad Reza Naghavi; Meisam Zargar (Current Plant Biology)
Ferula sp. has achieved widespread fame as a producer of specialized terpenoids used as raw materials in fragrances, food, cosmetics, and pharmaceutical industries. Since ancient times, Ferula species has been utilized to treat various health issues, such as asthma, toothache, inflammation, cancer, and digestive disorders. Besides, a growing body of research proves the healing efficacy of Ferula plants in treating modern diseases, such as multiple sclerosis (MS), HIV, and COVID19. The major challenge surrounding the commercialization of Ferula-derived terpenoids is their low quantity in Ferula plants. This necessitates the exploitation of approaches to circumvent this barrier and to enhance their production level to meet the continuous demands of industries for Ferula terpenoids. Recently, via functional genomics, omics technologies, and high-throughput analytical techniques, our understanding about terpenoid biosynthesis and regulation has been deepened, paving the way for the overproduction of target terpenoids. This review examines the potential of hairy root culture, CRISPR/Cas-mediated genome editing, and metabolic engineering, including gene overexpression and enzyme engineering, for enhancing Ferula capacity tailored to industrial and medicinal needs. The strategies present here, except hairy root culture, have never been proposed or applied in Ferula species. In its ultimate form, the proposed strategies are expected to reach large-scale terpenoid production.